Peningkatan kemampuan membaca pemahaman cerita menggunakan model pembelajaran examples non - examples dengan media visual pada peserta didik kelas IV sekolah dasar - Yolanda, Stefi; Winarni, Retno; Adi, Fadhil Purnama (Didaktika Dwija Indria, 2019)
Abstract. The purpose of this study is to improve reading comprehension by using learning models Examples Non - Examples with visual media. The form of this research is classroom action research and carried out in two cycles. The cycle consists of four steps, namely planning, action, observation, and reflection. The research subjects were homeroom teacher and fourth grade students. Data analysis technique is interactive analysis consisting of three components, namely data reduction, data display, and conclusion drawing. Data collection techniques used are documentation, observaation, interviews, tests. Data validity using data triangulation and technical triangulation. Based on the results of the study, it can be concluded that through the application of Examples Non - Examples with visual media can improve comprehension reading skills for IV students of SD N Bumi 01 Surakarta in the 2018/2019 academic year.Keywords : Examples Non-Examples Learning Model and visual media, reading comprehension ability of stories